In vitro Testing of the Trichoderma Species as Bio-control Agents of (Neofusicoccum. mangiferae .Crous) Pathogen of Branch Disease in Shade and Fruit Trees (Global Journal of Science Frontier Research, 2023)
This study carried out in 2013 to test the fungicidal potentiality of three Trichoderma species under laboratory condition The laboratory experiments were conducted at the laboratory of plant quarantine- Administration of Plant Protection Ministry of Agriculture Any Trichoderma specie was considered as treatment in addition to one synthetic fungicide Amstar-Top for comparison each treatment replicated 6 times and arranged in CRD The result revealed that Amistar-Top at concentration of 200 ppm had given significant inhibition compared with the three species of Trichoderma with different isolates of the pathogen However there was no significant difference between inhibition percentages from Amistar-Top in some treatments More over T harzianum with N mangiferae isolated from Mangifera indica and T viride with the fungal isolate from F benjamina were more effective than Amistar-Top
Keywords: trichoedrma spp; pathogen; neofusicoccum mangiferae crous; inhibition